2000
DOI: 10.1007/s001340051350
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of short-term mortality in critically ill patients with solid malignancies

Abstract: When transfer to an ICU is considered an option by patients and physicians, 30-day mortality is better estimated by an evaluation of acute organ dysfunction than by the characteristics of the underlying malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
77
3
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 0 publications
16
77
3
6
Order By: Relevance
“…Neutropenia was not found to affect mortality in cancer patients with Streptococcus pneumoniae bacteraemia [12], as well as bacteraemia caused by other micro-organisms [13]. In line with these data, five other studies evaluating patients hospitalised in ICU showed neutropenia to not be independently associated with mortality in cancer patients with different sites of infection [14][15][16][17][18]. During the past decades, the attention in management of infections in cancer patients has focused on fever and neutropenia [19].…”
Section: Discussionmentioning
confidence: 87%
“…Neutropenia was not found to affect mortality in cancer patients with Streptococcus pneumoniae bacteraemia [12], as well as bacteraemia caused by other micro-organisms [13]. In line with these data, five other studies evaluating patients hospitalised in ICU showed neutropenia to not be independently associated with mortality in cancer patients with different sites of infection [14][15][16][17][18]. During the past decades, the attention in management of infections in cancer patients has focused on fever and neutropenia [19].…”
Section: Discussionmentioning
confidence: 87%
“…Table 1 Principal admission diagnosis in ABMT/AHSCT patients (n ¼ 44) The outcome of allogeneic BM transplant patients with acute critical illness is described P Depuydt et al Short-term outcome in critically ill patients with solid cancer or haematological malignancy has been shown to be mainly predicted by the number of failing organs, rather than by the underlying neoplasy characteristics. 8,9,[23][24][25] Acute respiratory failure (ARF) with need for MV is the most common reason for ICU referral in these patients and is a very strong predictor for poor outcome. Moreover, whereas prognosis for mechanically ventilated cancer patients (including haematological patients) in general has improved over the last two decades, this trend has not been observed in ABMT/AHSCT patients, in whom ICU and inhospital mortality rates have not reduced below 80%.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, approximately 10 to 50 percent of cancer patients may experience AKI whom about 10 to more than 30% of them might need renal replacement therapy (RRT) during their hospitalization in intensive care unit (ICU) (20,21). In addition, melanoma, breast, lung, esophagus and colon cancers are the most common malignancies that could metastasize to kidney, leading to large, solitary mass lesions (22).…”
Section: Acute Kidney Injury In Cancersmentioning
confidence: 99%